2008
DOI: 10.1016/j.jfoodeng.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical behaviour of apple tissue in tensile and compression tests: Storage conditions and cultivar effect

Abstract: The micromechanical behaviour of apple tissue was studied using a miniature tensile stage positioned underneath a microscope that allowed for simultaneous acquisition of force-displacement curves while the deformation of the individual cells was followed and recorded. Tensile and compression tests were performed on small samples of apple parenchyma of two different cultivars (Jonagored and Braeburn) and two storage conditions (control and shelf-life). Tests on the repeatability of the methods has provided sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 23 publications
4
37
0
Order By: Relevance
“…The same characteristics of the stress-strain curves were observed in the Starkrimson apple samples. Similar stress-strain curves produced by tensile testing were found in [8,9] and the tissue curves show that the stress was low for small strain and increased with the increase of strain.…”
Section: Tensile Testsupporting
confidence: 76%
See 2 more Smart Citations
“…The same characteristics of the stress-strain curves were observed in the Starkrimson apple samples. Similar stress-strain curves produced by tensile testing were found in [8,9] and the tissue curves show that the stress was low for small strain and increased with the increase of strain.…”
Section: Tensile Testsupporting
confidence: 76%
“…Eckhard, et al did research on Elstar apple peel that was stored for a period of 14 days and found that the elastic modulus of Elstar peel with skin spots was higher than that of peel without skin spots under tensile tests; the values ranged from 30.5 Mpa to 50.6 Mpa [6]. In fact, the tensile strength and elastic strength obtained from the apple tissue that was subjected to the tensile test were small values, smaller than those of the apple peel [8,9]. This typifies the peel as the outermost layer of a fruit, protecting it from damage or destruction, but different peels have different mechanical properties.…”
Section: Tensile Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Feret's minimum diameter is a measuring method utilized to estimate the length or size of a cell or fiber (Briguet et al, 2004;Alamar et al, 2008). It is the minimum distance between two parallel tangents at opposite sides of the cell or fibers borders (Briguet et al).…”
Section: Bal Techniquementioning
confidence: 99%
“…Apple, being the third fruit in the world production ranking (FAO 2009), is the main subject of many studies aiming to understand the control of texture. Apple texture changes all along fruit development (Volz et al 2003) and markedly softens with ripening and post-harvest storage (Johnston et al 2002;Mehinagic et al 2004;Camps et al 2007;Varela et al 2007;Alamar et al 2008). The mechanisms involved are complex and imply several factors at different scales (Harker et al 1997a).…”
Section: Introductionmentioning
confidence: 99%